Pengaturan Pemberian Hak Upah Dalam Proses Pemutusan Hubungan Kerja dan Implementasinya Dalam Putusan Hakim - Dian Ekawati; Dadan Herdiana (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract This research aims to analyze the regulation of wage entitlements in the process of employment termination and their implementation in judge's decisions. The research question is